Ultrasound-Guided Lauromacrogol Injection for the Treatment of Active Bleeding After Renal Biopsy - Liu, Weizong; Jin, Chunchun; Lian, Qingshu; Xu, Lifeng; Lin, Zhanye; Lu, Jianghao; Gong, Xuehao (Frontiers in Pharmacology, 2021)
Background: This study aimed to describe the technique and outcomes of hemostasis for ultrasound-guided lauromacrogol injection for active bleeding after renal biopsy. Methods: Data from patients with active bleeding after renal biopsy between January 2018 and December 2020 were retrospectively collected. Patients who still had active bleeding after 30 mins of compression were then injected with lauromacrogol under ultrasound guidance. The patients’ symptoms before and after operation were collected to assess whether they had severe complications. Changes in hemoglobin and serum creatinine values were collected. Results: Data from a total of 15 patients with active bleeding after renal biopsy were collected, including data of 6 men and 9 women. After the operation, there were 11 cases of mild back pain; 1 case of chills, cold sweats, and back pain; 1 case of cold sweats and blood pressure reduction, and 2 cases with no obvious symptoms. No severe complications occurred in this study, and active bleeding was stopped in all patients. After the operation, compared with before the operation, there was no statistically significant difference in the hemoglobin value and serum creatinine value (P=0.10＞0.05, P=0.78＞0.05). Conclusions: Ultrasound-guided lauromacrogol injection is a relatively simple, safe and feasible method, which could be helpful in treating active bleeding in the immediate post-procedure period after renal biopsy.